Regional groupings among microstates - Andriamananjara, Soamiely (World Bank WashingtonUS, 1998)
Presents a model in which the decision to form, expand or join a regional grouping is based on negotiation costs and bargaining power rather than on the traditional costs and benefits of trade integration. Uses the case of the Caribbean Community (CARICOM) to show the model's relevance in the real world.